Switching activity in retail financial markets in Ireland - Papadopoulos, Alexandros; McGowan, Féidhlim; Timmons, Shane; Lunn, Pete (ESRI, 2023)
The present research investigates how consumers engage with the Irish financial retail market when choosing and switching financial products. Data were gathered from a nationally representative sample of 2,903 individuals who are involved in their household financial decisions. The study used interactive online tasks to record product ownership and switching rates for the main financial products in the Irish financial retail market (bank accounts, loans, credit cards and mortgages). It also assessed consumers’ behaviours related to their original product choice and when they consider whether to switch to another provider (e.g., Do they compare offers? Do they use online comparison tools?). Motivations for switching and potential barriers were also recorded. Switching activity was considered as a spectrum of decisions and actions, ranging from not knowing one could switch to having switched successfully. This approach allowed participants to be branched in the online survey to answer tailored questions based on their individual switching activity. The findings provide novel insight into the proportion of consumers progressing into each level of the switching process. Differences in consumers’ experiences of the process were explored based on switching activity, as well as socio-demographic characteristics. The results aim to identify where in the switching process better decisions can be encouraged and supported through policy interventions.